1983
DOI: 10.1346/ccmn.1983.0310202
|View full text |Cite
|
Sign up to set email alerts
|

Interlayer Cations as Reaction Directors in the Transformation of Limonene on Montmorillonite

Abstract: Abstract--Clays may catalyze chemical reactions by acting as Br6nsted acids, Lewis acids, and/or Lewis bases. The changes occurring when limonene (p-menthadiene) is heated in the presence of montmoriUonite illustrate how Brrnsted and Lewis acidity may operate competitively, the nature of the interlayer cations determining which reaction dominates. The rate at which the starting material disappears increases with the acidity of the clay, which depends upon the interlayer cations (Na < Mg < A1 < H). The concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The use of acid activated clays in the transformation of terpenes and the conversion of apinene to camphene and limonene is a well-documented test www.elsevier.com/locate/apcata Applied Catalysis A: General 318 (2007) 108-120 reaction [14][15][16] with which to evaluate the catalytic activity of the acid clays. Indeed, acid treated clays have been evaluated previously, in a non-systematic manner, for the production of pcymene [17,18].…”
mentioning
confidence: 99%
“…The use of acid activated clays in the transformation of terpenes and the conversion of apinene to camphene and limonene is a well-documented test www.elsevier.com/locate/apcata Applied Catalysis A: General 318 (2007) 108-120 reaction [14][15][16] with which to evaluate the catalytic activity of the acid clays. Indeed, acid treated clays have been evaluated previously, in a non-systematic manner, for the production of pcymene [17,18].…”
mentioning
confidence: 99%
“…Frenkel and Heller-Kallai (1983) showed that the products formed by the reaction of limonene over different ion-exchanged montmorillonites are functions of the interlayer cation.…”
Section: A Cshsmentioning
confidence: 99%